Study of motivational intensity in the search for the meaning of life in psychology majors - Cuny, José Antonio (2007)
This study aims at exploring motivational intensity in the search for the meaning of life, from a logotherapy perspective, in psychology students in a private university in Lima. The sample consisted of 100 students, ages from 18 to 26 years.Three instruments were utilized: Seeking Noetic Goal Test (SONG), a questionnaire of sociodemographic indicators and an autobiographical questionnaire. There were significant differences in scores of children of separated parents and deceased parents in comparison to students who live with both parents. In the qualitative assessment, students showed fear to death, loneliness and their future.